Crocus sativus (saffron) in the treatment of female sexual dysfunction: a three-center, double-blind, randomized, and placebo-controlled clinical trial - Ladan Kashani; Sahar Aslzadeh; Kamyar Shokraee; Ahmad Shamabadi; Borna Tadayon Najafabadi; Morteza Jafarinia; Sophia Esalatmanesh; Shahin Akhondzadeh (Mashhad University of Medical Sciences, 2022)
Objective: One of the traditional aphrodisiacs used in various cultures is Crocus sativus, commonly called saffron. Previous studies have pointed to the possible applicability of saffron for sexual dysfunction in both men and women. This study investigates the effects of saffron capsules on female sexual dysfunction.Materials and Methods: This study was a parallel-group, double-blind, randomized, placebo-controlled clinical trial. Participants, who were married women between 18 and 55 years of age suffering from severe sexual dysfunction, were randomized to receive either 15 mg Crocus sativus capsules twice daily or placebo. The treatment continued for 6 weeks, and patients were evaluated every 2 weeks. The primary outcome was the change in the female sexual function index score. Other outcomes included the female sexual function index sub-domains.Results: Seventy-four patients were equally randomized to each group, and 34 in each group completed the trial. Participants in both groups experienced improved total scores at each visit. However, a repeated-measures ANOVA revealed that time ´ treatment differed between groups in favor of the saffron group (p=0.050). During the 6th week follow-up, the saffron group had a 62% score improvement from baseline. Desire, lubrication, and satisfaction were female sexual function index domains in which saffron demonstrated superiority over placebo. The adverse event profile was similar for the groups, and no participant discontinued treatment.Conclusion: Findings of this study suggest that saffron might be a safe and effective option to ameliorate female sexual dysfunction. Further robust research is warranted.